AGROECOLOGICAL STRATEGIES FOR BIODIVERSITY: PROMOTING SUSTAINABLE FARMING SYSTEMS THROUGH ECOLOGICAL INTERACTIONS - Sawen, Diana; Rahimov, Shahram; Tursunov, Dilshod (Techno Agriculturae Studium of Research, 2026)
Intensive agricultural expansion has contributed to biodiversity loss, soil degradation, and reduced ecosystem resilience, raising urgent concerns for sustainable farming systems. Agroecological strategies offer an alternative approach by emphasizing ecological interactions and biodiversity-based farming practices. This study aims to analyze the role of agroecological strategies in promoting biodiversity and enhancing sustainability in agricultural systems. A qualitative-dominant mixed-methods design is employed using comparative ecological analysis, secondary biodiversity datasets, and field-based qualitative observations. Data are analyzed through comparative indicators of species richness, soil organic matter, pollinator abundance, and ecosystem resilience across conventional and agroecological farming systems. Results indicate that agroecological systems significantly outperform conventional systems, with higher species richness (8.4 vs 4.1), improved soil organic matter (5.7% vs 2.3%), greater pollinator abundance (92 vs 35 units/ha), and enhanced ecosystem resilience (0.88 vs 0.54). Findings also demonstrate improved yield stability and stronger ecological interactions in diversified farming landscapes. The study concludes that agroecological strategies play a critical role in enhancing biodiversity and promoting sustainable farming systems by strengthening ecological interactions and reducing dependency on external inputs, thereby supporting long-term agricultural resilience and environmental sustainability.